Oxytocin increases trust in humans with a low disposition to trust - Bodo Vogt; Paul Bengart; Caroylyn Declerck; Ernst Fehr (University of Zurich, Department of Economics, 2025)
In recent years, increasing skepticism regarding oxytocin's (OT) influence on social behavior arose. Low power, HARKing (hypothesizing after the results are known), and replication failures have clouded the field. Here, we directly address these concerns with a high-powered, preregistered study that offers robust evidence for a causal effect of OT on trust among individuals with a low disposition to trust. We recruited 359 low-trusting individuals who participated in a trust game under strict anonymity conditions. Results show that OT administration significantly increased trusting behavior by roughly 15%, with consistent effects across regression models with and without controls for personality traits. A pooled data analysis incorporating a previous sample (n=219) of low-trusting individuals further strengthens this conclusion, yielding a statistically significant 16.9% increase in trust. Crucially, no interaction effect was found between OT and the degree of dispositional trust, suggesting OT's effect is uniform across the low-trusting spectrum. These findings present a strong case for OT's selective trust-enhancing role. By isolating OT's impact within a well-defined subpopulation and experimental context, this study provides a critical pivot in the debate over neurobiological mechanisms of trust.
Keywords: 330; Hormon; Vertrauen; Soziales Verhalten; Experiment; Regressionsanalyse